A first look at spatially resolved infrared supernova remnants in M33 with JWST - Sarbadhicary, Sumit K.; Rosolowsky, Erik; Leroy, Adam K.; Williams, Thomas G.; Koch, Eric W.; Peltonen, Joshua; Smercina, Adam; Dalcanton, Julianne J.; Glover, Simon; Lazzarini, Margaret; Chown, Ryan; Donovan Meyer, Jennifer; et al. (The astrophysical journal, 2025)
We present the first spatially resolved infrared images of supernova remnants (SNRs) in M33 with the unprecedented sensitivity and resolution of JWST. We analyze 40 SNRs in four JWST fields: two covering central and southern M33 with separate NIRCam (F335M, F444W) and MIRI (F560W, F2100W) observations, one ∼5 kpc-long radial strip observed with MIRI F770W, and one covering the giant H II region NGC 604 with multiple NIRCam and MIRI broad/narrowband filters. Of the 21 SNRs in the MIRI (F560W+F2100W) field, we found three clear detections (i.e., identical infrared and Hα morphologies), and six partial-detections, implying a detection fraction of 43% in these bands. One of the SNRs in this field, L10-080, is a potential candidate for having freshly formed ejecta dust, based on its size and centrally concentrated 21 μm emission. In contrast, only one SNR (out of 16) is detectable in the NIRCam F335M+F444W field. Two SNRs near NGC 604 have strong evidence of molecular (H2) emission at 4.7 μm, making them the farthest known SNRs with visible molecular shocks. Five SNRs have F770W observations, with the smaller younger objects showing tentative signs of emission, while the older, larger ones have voids. Multiwavelength data indicate that the clearly detected SNRs are also among the smallest, brightest at other wavelengths (Hα, radio, and X-ray), have the broadest line widths (Hα FWHM ∼ 250-350 km s−1), and the densest environments. No correlation between the JWST-detectability and local star formation history of the SNRs is apparent.
Veröffentlicht: 11. August 2025
Gesehen am 21.01.2026